From Strategy to Action: Transforming Organizational Goals into Organizational Behavior - Gagné, Marylène (2018)
The purpose of this paper is to develop a conceptual model to explain and predict how organizational goals are transformed into organizational behavior. Using the theory of action phases as the overarching framework to explain how organizations and employees commit to goals and successfully pursue them, in conjunction with self-determination theory to explain the development of goal commitment at the individual level, a motivational model of organizational goal pursuit is proposed. This model takes into consideration mission and strategic goal development, organizational-level implementation intentions in the form of strategic plans and dynamic capabilities, individual goal internalization, and implementation plans at the individual level. These goal phases are proposed to be affected by the attraction, selection, socialization and management of organizational members. The model can serve to develop knowledge in the area of behavioral strategy by integrating motivational considerations into strategic management models.